Do Trading Partners Still Matter for Nigeria's Growth? : A Contribution to the Debateon Decoupling and Spillovers - Obiora, Kingsley (IMF Working Papers; Working Paper ;, 2009)
Should policymakers still be concerned about economic growth in trading partners? Have developing and emerging market countries decoupled from the US enough to grow despite significant recession in the US? Using VAR models, this paper addresses these questions for Nigeria in the context of the global crisis. The results seem to debunk the "decoupling theory" and suggest there are still significant spillovers from Nigeria's main trading partners, including the US, with trade and commodity price linkages being the dominant transmission channels. Given the sharp fall in both trade financing and commodity prices in aftermath of the crisis, these results provide some explanation to the realization of adverse second-round effects in Nigeria.